3D Printing of natural sandstone at pore scale and comparative analysis on micro-structure and single/two-phase flow properties. (15th December 2022) - Song, Rui; Wang, Yao; Tang, Yu; Jiajun peng; Liu, Jianjun; Yang, Chunhe
Abstract: As the first effort in literature, the 3DP sample from the micro-CT image of a natural sandstone in this study achieves the printing resolution of 2 μm. The pore structure of both the 3DP and original sample are analyzed comparatively, as well as the pore size distribution (PSD), porosity, and absolute permeability by DRP simulation. The visualized CO2 displacing oil experiment on the 3DP sample are conducted, and compared with the experimental benchmark data. The results indicate that: 1) The PSNR of the 3DP S1 is in [9.010, 14.983], and its SSIM is in [0.870, 0.925]. Most pore features are printed but some are not in its original size or position. 2) The porosity and permeability of the 3DP sample are 10.01% and 27.81mD, showing a decline of 2.91% and 32.49mD compared to the original sample. 3) Two primary causes for the mismatching of the pore structure are confirmed, including insufficient removal of uncured resin, and shrinkage effect in light curing process. 4) Most contact angles of oil in 3DP sample lie in [0°, 90°], indicating it is oil-wetted. This study provides a new tool for the quantitative characterization and accurate understanding of the mobilization and residual mechanism of the multiphases in porous rock. Highlights: The 3DP sample is manufactured at resolution of 2 μm from natural sandstone. The PSNR of the 3DP sample is in [9.010, 14.983], and its SSIM is in [0.870, 0.925]. Most pore features are printed but some are not in its original size or position. Visualized CO2 displacing oil experiments on the 3DP sample are conducted.